Pre-treatment of Dryopteris cristata (L.) A. Gray rhizome as a method of elimination of contaminants and explant browning micropropagation - Zenkteler, Elżbieta; Kwaśna, Hanna (Biodiversity: Research and Conservation, 2007)
Micropropagation of Dryopteris cristata (L.) A. Gray by rhizome explants requires a pre-treatment procedure as a <<stage 0>>. Mycological examinations of fungi from fern rhizomes allowed to determine 24 species represented by 66 isolates and a group non-sporulating colonies. Most frequently fungi were represented by Cylindrocarpon destructans and Mycelium radicis atrovirens. The pre-treatment procedure reduces exogenous and endogenous contamination by fungi, actinomycetes and other bacteria in developing adventitious buds. Starvation of rhizomes during pre-treatment significantly reduces starch and phenolic contents and thereby prevents browning of the explants. The present data revealed that in decontaminated, actively growing buds there are less phenolics than in contaminated rhizomes.